The relationship between principal transformational leadership practices, teacher organizational commitment, and school culture in Primary Cluster Schools in Selangor / Jeyasushma Veeriah - Jeyasushma , Veeriah (2017)
The Malaysian Education Blueprint 2013 – 2025 clearly specifies on ensuring highperforming school leaders in schools. One of the strategies for accelerating excellence through educational institutes is seen in the establishment of cluster schools of excellence. The purpose of this study is to examine the relationship between principal transformational leadership practices and teacher organizational commitment in primary cluster schools in Selangor, both directly and indirectly with the mediation of school culture. This is a non-experimental quantitative research using the survey technique. Data is collected through the administrations of a set of questionnaires focusing on demographic profiles, principal transformational leadership practices, teacher organizational commitment, and school culture. A total of 331 returned and valid questionnaires were analysed. The study affirms the key role of principals in enhancing teachers’ organizational commitment in creating and managing the school culture. The findings revealed that teachers perceived their principals to practice high levels of transformational leadership. They also perceived highly on their school culture. However, teachers rated themselves of being moderately committed. The Pearson Product-moment correlation analysis was used to test the relationships between variables. Findings also showed a statistically significant and positive correlation that is strong between the principal transformational leadership and teacher organizational commitment, and school culture. The correlation between school culture and teacher organizational commitment was statistically significant and positive at a moderate strength. Using the multiple regression analysis, the transformational leadership dimensions of strengthening school culture and widely-shared vision were identified as significant predictors of teacher organizational commitment. Additionally, the mediation analysis was carried out using the PROCESS macro for SPSS. Results from the analysis showed that school culture partially mediates the relationship between principal transformational leadership practices and teacher organizational commitment. Subsequently, the structural equation modeling (SEM) with AMOS (Analysis of Moment Structures) was used to determine the model fit of the data gathered. The respecified structural model fits the data collected from primary cluster schools in Selangor. Overall, the main findings illuminate the influence of principal transformational leadership practices on teacher organizational commitment, directly and through school culture. Finally, with the significant changes our education system is facing, school principals have important roles in managing and administering schools. Therefore, the findings of this study can be used to increase the knowledge in the educational leadership field.